Metode Muhasabah: Analisis Pendekatan Psikologi Sufistik Perspektif Al –Ghazali: (Konsep Pendidikan Ruhaniyah Melalui Tazkiyatun nafs) - Mutmainah Mutmainah (STAI Syaichona Moh. Cholil Bangkalan, 2021)
The objectives of this study include to find identify the muhasabah method in the Sufistic psychological understanding according to al Ghazali, and to find out the implications of the Muhasabah method in understanding Sufistic psychology as the concept of spiritual education through tazkiyatun nafs. This research method is literary or library research, and is descriptive qualitative in nature, by examining literature sources related to muhasabah. Data analysis techniques with the Milles and Huberman model include: data reduction, data display, and conclusion drawing. The result of this research is that Sufistic psychology as the study of human behavior is related to human nature from a spiritual perspective based on the perspective of Sufism according to the Koran and al-Hadith. There are six stages in muhasabah according to al Ghazali, among others: first is musyarathah (stipulation of conditions), second is muraqabah (supervising), third is muhasabah (self-introspection), fourth is mu'aqabah, fifth is mujahada (earnest), and the sixth is mu'atabah (self-deprecation). The implication of the muhasabah method in the Sufistic psychological approach as a concept of spiritual education towards insanul kamil is how the self-introspection method brings human life more meaningfully by performing self-cleansing (tazkiyatun nafs) so that humans have a new existence, both in speech, attitudes and behavior as insanul kamil.